Factors influencing street use frequency and evaluation of street image in densely built-up areas: a case study in Shinyo neighborhood, Nagata Ward, Kobe. Issue 5 (3rd September 2021) - Yoshihara, Takumi; Tanaka, Takahiro; Inachi, Shusuke; Saito, Hiroaki
ABSTRACT: Narrow streets in densely built-up areas face problems in terms of disaster prevention. However, such streets serve as spaces for activities, communication, and a comfortable lifestyle, and thus, such streets should be considered for redesign in view of their beneficial aspects. Therefore, this study aims to examine the physical characteristics of these beneficial streets and discuss their relationship with the frequency of street use; in addition, street images were also analyzed. The results indicate that it is conceivable for street spaces with beneficial aspects to be created such that physical environmental factors can be controlled.